Research and Application on Microservices Architecture in Civil Affairs Informatization. (June 2020) - Tao, Liang; Fan, Yida; Zhang, Tong; Zhao, Chao; Yang, Tianrong
Abstract: With the development of information technology, microservices have been applied to more and more industries. Firstly, we introduce microservices and microservices architecture, analyse the main problem of civil affairs informatization, and explain the composition of microservices architecture. Secondly, we give the key technology of microservices which include abstract methods of microservices, microservices process management and the schedule of microservices workflow. Finally, we talk about the situation of civil affairs applications for using microservices architecture and give the conclusion.